The evaluation of a BCG vaccine against bovine tuberculosis in African buffaloes (Syncerus caffer) - Kriek, N.P.J. (University of Pretoria, 2013)
Dissertation (MSc (Tropical Diseases))--University of Pretoria, 2004.